METODOLOGI KRITIK HADIS: (STUDI TAKHRIJ AL-HADIS DAN KRITIK SANAD) - Nasrullah, Nasrullah (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with methodology of hadith criticism focusing its study on takhrij al-hadis and sanad criticism. Hadith has been agreed as one of Moslem’s sources of teachings after the Qur’an. Its position is very central since hadith is a direct interpretation and is a continuity of what is found in Qur’an. Nevertheless, hadith differs from the Qur’an since the status of the latter is always mutawatir. In addition, the position of hadith always differs from one another since the system of transmission is not always congregation (mutawatir). This difference causes a hadith to have different status from another. Therefore, a methodology of hadith criticism plays an important role to decide the validity of a hadith. Kata Kunci: kritik hadis, takhrij al-hadis, siqah, dabit, sahih, sahabat, riwayat